Investigating the prevention and mitigatory role of risk communication in the COVID-19 pandemic: a case study of Bloemfontein, South Africa - Kunguma, Olivia; Mokhele, Mosekama O.; Coetzee, Mercia (AOSIS, 2021)
The South African disaster response activities surpass risk reduction since the implementation of the Disaster Management Act 57 of 2002 (DMA) and the National Disaster Management Framework of 2005 (NDMF). Risk reduction, in particular risk communication, remained unexploited until the occurrence of coronavirus disease 2019 (COVID-19) pandemic. The legislation and policy mandate a proactive approach for disaster management, requiring a focus on disaster risk reduction. Therefore, this study aimed to assess the significance of risk communication as a critical prevention and mitigatory strategy in disaster risk management, focusing on the COVID-19 pandemic. Key to risk communication success is ensuring adequate comprehension, accurate perception of the disseminated information, and compliance with regulations. Questions of trustworthiness, acceptability, effectiveness, and usefulness of messages and strategies communicated sought answers from the Bloemfontein population. Furthermore, the Agenda-setting Theory provided the grounding for the study. The study sample was picked in a stratified random sampling manner, using the confidence level and margin of error equation. A questionnaire survey was used to collect the data required to achieve the research objectives. Risk communication as a disaster risk reduction strategy implemented concurrently with imposed regulations was found to have played a vital role in mitigating the virus spread. However, the respondents were not aware of the local disaster management centre, which is supposed to be engaged in COVID-19 disaster management activities.
Keywords: COVID-19; Risk communication; Disaster management; Legislation; Policy; Media; Disaster communication; Agenda-setting Theory